Monitoring data of the Høje Taastrup water pit thermal energy storageZenodo - Ioannis Sifnaios; Simon Furbo; Adam R. Jensen (Data in Brief)
The pit thermal energy storage (PTES) in Høje Taastrup, Denmark, was the first large-scale PTES to be operated as a short-term storage (storage cycle of 1-2 weeks). The storage was connected to the Copenhagen district heating grid and started operating in February 2023. In addition to the unique use case, the storage represents the state-of-the-art PTES system, featuring an innovative lid construction and a custom-developed polymer liner. Monitoring data of the storage operation are provided freely for 2024, including measurements of the storage water temperature, charged/discharged energy, diffuser flow rates and temperatures, lid heat flux, humidity, and temperatures, soil temperature, and ambient conditions. The dataset can be used to assess the storage performance and, more importantly, validate simulation models, which has not been done for short-term PTES systems. The data is freely available on GitHub.